Locally resonant metasurface for low-frequency transmissive underwater acoustic waves - Chen, Zhong; Guan, Shenghong; Xie, Qiang; Li, Zheng; Gao, Zhongmei; Negahban, Mehrdad (Frontiers in Physics, 2023)
Acoustic metasurfaces for underwater wave manipulation have great potential use, but the strong solid-fluid interaction caused by impedance closeness between the structure and water becomes an obstacle, especially in the low-frequency range. Here a locally resonant metasurface for transmissive underwater acoustic waves is proposed for which each metasurface unit consists of one channel and 3 subunits. Each subunit has one plate and two rubber spacers to form a resonator. By changing the height ratio of the plate over the subunit, arbitrary phase shifts within the full 2π coverage can be obtained at will with transmission ratio always higher than 60%. Three applications, including asymmetric transmission, self-bending and source illusion, are chosen to validate the design methodology. Compared with previous transmissive type underwater metasurface, this design has the advantage of low frequency and simple fabrication. This work provides a novel paradigm of modulating waves for ocean exploration, underwater communication, and submarine stealth and antidetection.